2019
DOI: 10.1590/0100-6991e-20192096
|View full text |Cite
|
Sign up to set email alerts
|

Impacto das complicações pós-transplante simultâneo pâncreas-rim sobre o custo da internação hospitalar.

Abstract: Objective: considering simultaneous pancreas-kidney transplantation cases, to evaluate the financial impact of postoperative complications on hospitalization cost. Methods: a retrospective study of hospitalization data from patients consecutively submitted to simultaneous pancreas-kidney transplantation (SPKT), from January 2008 to December 2014, at Kidney Hospital/Oswaldo Ramos Foundation (Sao Paulo, Brazil). The main studied variables were reoperation, graft pancreatectomy, death, postoperative complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to a study conducted outside of China ( 12 ), the hospitalization costs ranged from $75,200 to $87,800 and the laboratory testing costs were $23,600–$11,200 for patients undergoing SPKT, and the above expenditures did not include the organ acquisition costs. The high hospitalization expenses pose a huge financial challenge to SPKT patients ( 13 ). In addition, bleeding, thrombosis, and infections after SPKT are the main causes of prolonged hospitalization, and the incidence of readmission reached 74.2% in SPKT patients due to various infections ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted outside of China ( 12 ), the hospitalization costs ranged from $75,200 to $87,800 and the laboratory testing costs were $23,600–$11,200 for patients undergoing SPKT, and the above expenditures did not include the organ acquisition costs. The high hospitalization expenses pose a huge financial challenge to SPKT patients ( 13 ). In addition, bleeding, thrombosis, and infections after SPKT are the main causes of prolonged hospitalization, and the incidence of readmission reached 74.2% in SPKT patients due to various infections ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main causes of prolonged hospital stay and high hospitalization costs for acute-care hospital patients are related to development of complications, such as an infectious disease 1 . It has also been shown that prolonged hospitalization of general internal medicine inpatients is associated with higher costs and complication rates because of nosocomial infections 2 , and that postoperative complications such as infection increased the cost of hospitalization for patients who underwent a simultaneous pancreas-kidney transplantation 3 . Additionally, a strong relationship among hospitalization costs, healthcare resource utilization, and postoperative complications following a lower anterior resection procedure for rectal cancer has been demonstrated 4 .…”
Section: Introductionmentioning
confidence: 99%